Synthetic approaches towards thioester-mediated biocojugation and lanthanide-based glycoconjugate probes - Burke, Helen M. (Trinity College (Dublin, Ireland). School of Chemistry, 2017)
This thesis, entitled "Synthetic Approaches Towards Thioester-Mediated Bioconjugation and Lanthanide-Based Glycoconjugate Probes" is divided into six chapters. Chapter 1, the introduction, firstly introduces the concept of bioconjugation and the use of conjugation strategies to improve current therapeutics. A brief overview of two protein post-translational modifications (PTMs), ubiquitination and glycosylation is then given with the implications of such bioconjugation discussed. Following this, the importance of access to sufficient quantities of homogeneous, post-translationally modified glycopeptides is described with the formation of O- and A-linked glycopeptides discussed, both biosynthetically and chemically. The remainder of this chapter is divided into two sections; the first of which serves to introduce peptide synthesis. The significant advances in peptide synthesis and chemical ligation strategies are outlined with their use for the incorporation of post-translational modifications included. Particular emphasis is placed on native chemical ligation (NCL) with some of the strategies introduced to address NCLs main limitations reviewed. The last section of this chapter delivers an overview of the carbohydrate-active glycosidase enzymes with their synthetic applicability briefly mentioned. The chapter concludes by outlining examples of the current glycoconjugate probes used for the detection of the biologically relevant glycosidase enzymes
Keywords: Chemistry, Ph.D.; PhD Trinity College Dublin, 2017